PHYSIOTHERAPEUTIC METHODS IN THE TREATMENT OF DYSAPAREUNIA: A NARRATIVE REVIEW (CIPEEX, 2024)
Introduction: Dyspareunia is defined as genital pain. It can affect both sexes, but it is more common among the female population. This disorder impacts a woman's quality of life, sexual relationship, and even the performance of gynecological exams. Sexual dysfunctions affect important aspects of life, including desire, pain during sex, and orgasm. Physiotherapy offers treatments that encompass a variety of techniques, exercises, and behavioral approaches. Objective: To promote awareness of physiotherapeutic methods in dyspareunia and identify the most common female sexual dysfunctions. Methodology: This article involved a narrative literature review with a qualitative focus, aiming to analyze and comprehensively describe issues related to the impact of dyspareunia on women's quality of life and explore the physiotherapeutic approaches used to treat these disorders. Results: It was observed that women who sought treatment through urogynecological physiotherapy experienced significant improvements in their pain complaints. These improvements were related to increased muscular awareness in the pelvic region resulting from the application of physiotherapeutic methods. Conclusion: It can be concluded that urogynecological physiotherapy is an effective approach to treating dyspareunia in women. The positive results highlight its importance in improving sexual quality of life. It is essential to promote awareness of this therapy and ensure access to it for the sexual and overall well-being of women.